MENINGKATKAN PEMAHAMAN MAHASISWA PADA MATA KULIAH KONSEP DASAR IPA MENGGUNAKAN MODEL PEMBELAJARAN CBSA DENGAN PENDEKATAN DISCOVERY - Subuh Anggoro; Badarudin Badarudin (Khazanah Pendidikan, 2008)
This research is aimed at finding out whether students’ active learning with discovery approach could improve the students’ understanding of basic science subject. The research used survey method. The population of this research was students who took the subject of Konsep Dasar IPA (the Basic Concept of Science) out of which one class was taken as sample. The data was then analyzed with descriptive technique with the help of graph. The result showed that 72% did not have sufficient understanding about the topic of energy and its transformation which was delivered without the help of learning aid and discussion. After learning aid was and discussion was facilitated by the lecturer, all the subjects of this research expressed their better improved understanding. Discovery method with experiment and discussion is crucial in helping students understand the basic concept of science. Key words: understanding, basic concept of science learning, students’ active learning, discovery technique.